2003
DOI: 10.3748/wjg.v9.i9.1904
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of octreotide on gastric cancer growthviaMAPK pathway

Abstract: Inhibition of sequential molecular events in MAPK pathway may interpret the mechanisms underlying the effect of octreotide on the growth of gastric adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…6,10 The antineoplastic action of octreotide is thought to be mediated through the receptors for SST that may trigger the MAPK pathways. 11,12 Cellular proliferation is achieved through entry of cells from G 0 into the active cell cycle, whereas progression through the cell cycle is controlled by a spectrum of regulatory proteins. COX-2 or SST may modulate expression of a cascade of genes that control cell proliferation at different site of intracellular pathway.…”
mentioning
confidence: 99%
“…6,10 The antineoplastic action of octreotide is thought to be mediated through the receptors for SST that may trigger the MAPK pathways. 11,12 Cellular proliferation is achieved through entry of cells from G 0 into the active cell cycle, whereas progression through the cell cycle is controlled by a spectrum of regulatory proteins. COX-2 or SST may modulate expression of a cascade of genes that control cell proliferation at different site of intracellular pathway.…”
mentioning
confidence: 99%
“…10 Although the anti-neoplastic mechanisms behind rofecoxib and octreotide are different, they may synergistically inhibit the AP-1 pathway, showing a close association with the signal transduction pathways of oncogene and therefore affecting the proliferation of tumor cells. 17,18 In the present study, celecoxib at low dose combined with octreotide was able to arrest the growth of SGC-7901/ ADR cells significantly as well. The combination strategy showed a greater growth inhibition of the Adriamycin-resistant cell SGC-7901/ADR than by celecoxib alone.…”
Section: Discussionmentioning
confidence: 77%
“…15 So it is important for the treatment of A B C D only in most neuroendocrine neoplasms, 16 but also in those tumors that originate from the central nervous system, breast, and lung. [17][18][19] It was reported that SSTR2 expressed in gastric cancers, and SSTR2, SSTR3 mRNA expressed in gastric cancer cell line SGC7901, 20,21 which belongs to moderate-differentiated adenocarcinoma. But little is known about the expression and function of the human SSTR3 in human gastric cancer tissues.…”
Section: Discussionmentioning
confidence: 99%